Environmental issues and financial reporting trends: A survey in the chemical and oil & gas industries - Roberta Salomone; Giulia Galluccio (Fondazione Eni Enrico Mattei (FEEM), 2001)
As environmental performance is increasingly seen to have an influence over financial performance and financial risk assessment, disclosure of environmental issues in the Annual Reports is a fundamental requirement for a company in order to satisfy the information needs of its stakeholders. Given this pressure there is a definite trend among leading companies to report their environmental performances within the financial statements, but the way companies disclose environmental-related information varies from company to company and from country to country. Besides, the qualitative level of this kind of disclosure, in term of relevance, comparability and credibility, is not generally very high. More and more voluntary and regulatory guidelines are emerging to encourage companies to disclose environmental issues in Annual Report. The aim of this paper is to examine literature relating to environmental disclosures in the Annual Report and to identify this environmental disclosure, but also its location and typology, thereby defining current practices on environmental reporting in Annual Reports of selected firms in the chemical and oil &gas industries.
Keywords: M14; M40; 330; Corporate culture; social responsibility; environmental accounting; environmental responsibility; Umweltmanagement; Geschäftsbericht; Bilanzierungsgrundsätze; Chemieindustrie; Mineralölwirtschaft; Industriestaaten